Construction Management Analysis of Cikeruh Steel Box Girder Bridge Project Spanning 80m Cirebon – Bandung Highway Majalengka Regency - Dion Iskandar; Dynia Shalihatin Alfitri; Fadli Fahrizal; Saihul Anwar (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This study aims to analyze the construction management of the 80-meter Cikeruh Steel Box Girder Bridge Project on the Cirebon-Bandung Highway in Majalengka Regency, which is a replacement for the old bridge due to the age of the structure and increased vehicle load intensity. This construction management analysis includes calculating the volume of work, estimating the budget plan (RAB), and scheduling project implementation. The research method used is qualitative with direct observation, interviews, and literature study techniques. The data collected includes primary data (field technical data, working drawings) and secondary data (location maps, unit price analysis, and unit prices). The AHSP used in this study is the 2024 Majalengka Regency AHSP. The results of the analysis of the main work volume calculations show a bore pile volume of 89.49 m3, a pile cap volume of 134.4 m3, a column volume of 50.2656 m3, and a pier head volume of 56000 m3. Based on the RAB calculations, the total cost required to complete the project is IDR 31,149,328,054.56. The work schedule was analyzed using a Bar Chart and S-Curve. This study provides a comprehensive overview of the essential aspects of volume, cost, and time in bridge construction project management.